Factoring - financial instrument supporting the current activity of an enterprise - Dorota Czerwińska-Kayzer; Anna Bieniasz (Journal of Agribusiness and Rural Development, 2009)
Small and medium enterprises have a difficult access to classic financial sources. Therefore the factoring could be a financial instrument supporting effective management of the liabilities. Factoring improves the financial situation of a company, first of all financial liquidity. Moreover, factoring improves structure of financial statement and creates a possibility of risk transfer of debtor insolvency on factor.